(untitled) (Journal of Engineering, 2009)
Piezoelectric transducers have become increasingly popular in vibration control applications. They are used as sensors and as actuators in structural vibration control systems. They provide excellent actuation and sensing capabilities. In this paper, the term smart beam refers to a beam with a finite number of collocated piezoelectric actuator / sensor pairs. The proposed thin smart beam governing equation was derived by the same procedure that the Bernoulli-Euler equation derived but with some additional mathematical terms to be valid for describing the smart beam. The engineering control techniques were used to obtain the solution of the proposed differential equation for the simply supported beam where with some auxiliary equations and modifications a block diagram for any type of applied load (static, or cyclic) as the input and the beam deflection as the output was constructed. For insuring an efficient reduction in the beam deflection an integrated system with a high voltage amplifier and lead controller was designed. Many cases were studied and simulated including the variation of load nature and its frequency, and the number of collocated piezoelectric actuator/sensor pairs and in all cases a valuable deflection reductions were obtained.